Dietary sodium, potassium intake, sodium-to-potassium ratio and risk of hypertension: a protocol for systematic review and dose–response meta-analysis of cohort studies - Qian Wu; Yingtian Yang; Qianyu Lv; Junjia Li; Lanlan Li; Shihan Wang (BMJ Open)
Introduction Hypertension (HTN) is the leading cause of disease and death on a global scale. Diet’s sodium and potassium levels may synergistically affect blood pressure. Currently, the sodium-to-potassium (Na/K) ratio is becoming a more reliable indicator. There has not been a systematic investigation of the dose–response relationship between dietary sodium, potassium, the Na/K ratio and the incidence of HTN based on the same study criteria. This study will conduct a thorough dose–response meta-analysis of cohort studies to estimate the effects of dietary sodium, potassium, and the Na/K ratio on the incidence of HTN to provide the most accurate reference for sodium and potassium intake.Methods and analysis We will identify all relevant prospective and retrospective cohort studies by searching PubMed, Embase and Web of Science (from inception until December 2022). Exposures are 24 hours urinary excretions, and the outcome is the incidence of HTN. Two researchers will perform the literature selection and data extraction separately. The Newcastle-Ottawa Scale will be used to evaluate the quality of the included studies. We will use both linear and non-linear regression models to investigate the dose–response relationship among different levels (≥3) of sodium, potassium, Na/K ratio intake and the incidence of HTN (OR/RR/HR). Subgroup and sensitivity analyses will be applied to assess the potential heterogeneity sources and examine the stability of the results. We will also evaluate heterogeneity across studies and publication bias. Stata V.15.0 and RevMan V.5.0 will be used for statistical analyses.Ethics and dissemination According to the Institutional Review Board/Independent Ethics Committee of the Guang'anmen Hospital of the China Academy of Chinese Medical Science, this systematic meta-analysis protocol does not require ethical approval or informed consent. This meta-analysis will be published in a scientific journal with peer reviews.PROSPERO registration number CRD42022331203.